2010
DOI: 10.1002/mc.20695
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses human papillomavirus oncoproteins, restores p53, rb, and ptpn13 proteins and inhibits benzo[a]pyrene‐induced upregulation of HPV E7

Abstract: Curcumin has great potential as a chemopreventive and chemotherapeutic agent; however, its effects on human papillomavirus (HPV)-associated molecular events are inadequately explored. This study examined the effects of curcumin on HPV-associated pathways involved in developing cervical cancer. We demonstrate for the first time that curcumin treatment suppresses cervical cancer cell growth in a three-dimensional raft culture system. Curcumin also inhibits tumorigenic characteristics as shown by decreases in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 37 publications
5
82
1
1
Order By: Relevance
“…Several preclinical and clinical studies indicated the anticancer potential of curcumin (Basu et al, 2013;Dai et al, 2013;Yin et al, 2013). Curcumin exhibited its antitumor action in HPV associated cervical cancer (Basu et al, 2013) by restoring p53 and pRb (Maher et al, 2011) and by reducing the level of cyclin D1 and activation of tumor suppressor proteins (Singh and Singh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical and clinical studies indicated the anticancer potential of curcumin (Basu et al, 2013;Dai et al, 2013;Yin et al, 2013). Curcumin exhibited its antitumor action in HPV associated cervical cancer (Basu et al, 2013) by restoring p53 and pRb (Maher et al, 2011) and by reducing the level of cyclin D1 and activation of tumor suppressor proteins (Singh and Singh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The CM treatment also activated caspase À3 and À9 as well as downregulated COX-2, iNOS, and cyclin D1 in HeLa, SiHa, and CaSki cell lines (Singh and Singh, 2009). Furthermore, the CM suppressed HPV16 E6/E7 and increased the expression of tumor suppressor proteins p53 and Rb, protein tyrosine phosphatase and non-receptor type 13 (PTPN13), and also inhibited benzopyrene-induced upregulation of HPV E7 in HeLa, SiHa, C33a, and CaSki cervical cancer cell lines (Maher et al, 2011).…”
Section: Anticervical Cancer Activity and Cell Apoptosis Induced By Cmentioning
confidence: 99%
“…In clinical trials, intravaginally administered Praneem, a polyherbal formulation, was shown to eliminate HPV16 infection in early cervical intraepithelial lesions [71]. Methyl jasmonate, soyasaponin, phytoglycoprotein, curcumin, silymarin, withaferin A, and epigallocatechingallate (EGCG) showed therapeutic effects via repression of viral oncogenes, upregulation of tumor suppressor genes, or induction of apoptosis in vitro [72,73,74,75,76,77,78]. Withaferin A treatment reduced tumor volume by approximately 70% in a xenograft model.…”
Section: Therapeutics Against Hpvsmentioning
confidence: 99%